Optimizing the Integration of a Biopesticide (Bacillus subtilis QST 713) with a Single-Site Fungicide (Benzovindiflupyr) to Reduce Reliance on Synthetic Multisite Fungicides (Captan and Mancozeb) for Management of Apple Scab - Ayer, K M (Plant disease, 2021)
Apple scab is one of the most economically important diseases of apple in temperate production regions. In the absence of durable host resistance in commercially preferred cultivars, considerable applications of fungicides are needed to manage this disease. With the sequential development of resistance to nearly all classes of single-site fungicides in the apple scab pathogen Venturia inaequalis, synthetic multisite fungicides, such as mancozeb and captan, often comprise the core of chemical management programs for apple scab. Although these fungicides have demonstrable benefits for both disease and fungicide resistance management, the sustainability movement within agriculture aims to reduce reliance on such fungicides because of their broader environmental impacts. In this study, we establish a framework to enhance the feasibility of chemical management programs that do not rely on use of synthetic multisite protectant fungicides to manage apple scab. Specifically, we wish to evaluate chemical programs that integrate the biopesticide Bacillus subtilis QST 713 (Serenade Opti) in rotation with benzovindiflupyr (Aprovia), a single-site fungicide belonging to the class of succinate dehydrogenase inhibitors (SDHI), to circumvent the need for applications of synthetic multisite fungicides. During implementation of these programs, disease incidence data were taken at biweekly intervals. Regardless of the seasonal challenges presented in the 2 years of this study, when Bacillus subtilis QST 713 was used in place of captan and mancozeb mixtures, we did not observe any significant differences (P > 0.05) in development of apple scab symptoms between any of the management programs for the vertical axis or super spindle orchards in either year. This potential for substituting synthetic multisite fungicides with biopesticides is best realized when the programs are used with a decision support system in a super spindle planting system, where trees have reduced canopy densities. This 2-year study shows the potential to achieve adequate disease control using the integration of SDHI fungicides and biological controls without the use of synthetic multisite fungicides